Identification and Application of Good Corporate Governance Principles in the Guarantee industry in Indonesia - Antoni Ludfi Arifin; Resista Vikaliana; Wahyuddin Latunreng; Abdul Bari (International Journal of Social Science and Business, 2022)
Indonesia is a country that is very committed to the implementation of good corporate governance in every organization and business. To that end, we have conducted studies that are supported by secondary research data published in many book journals and other website documents. The purpose of this study is to analyze the data critically by involving data evaluation and coding, concluding to obtain valid and up-to-date data findings. This type of research is qualitative. This research approach uses a phenomenological approach. The data collection method uses documentation analysis. The technique used to analyze the data is descriptive qualitative analysis. The results of the research are good corporate governance used in guarantee institutions for each, which is a decision and management of a company that adheres to the principles to be purchased, high transparency, responsibility, high self-management, fairness and sustainability. In this case, the purpose of the application is to create for all parties in business activities so that the business runs well, accountable and profitable in an economic context.